N-glycan signatures of immunoglobulins-depleted serum proteins in colorectal cancer - Huiai Lu; Yuanyuan Liu; Yi Wang; Jiajing Lin; Liming Cheng; Xin Liu; Si Liu; at (Glycoconjugate Journal, 2026)

Substrate filling ratio affects nitrogen removal and antibiotic resistance risk in modular moving bed constructed wetland: Biofilm-mediated microbial community succession and resistome profiles reshaping - Lei Zhou; Jiawei Xie; Liming Zhang; Lingwei Kong; Ping Deng; Jianshi Huang; Weicong Wang; Shuangqi Wu; Shengbing He; Shuiping Cheng (Environmental Research, 2026)

Development and application of a creep model of rock mass based on memory-dependent derivatives - Liming Zhang; Yanchen Cheng; Zaiquan Wang; Shengchang Liu; Jinhao Wen; Fanzhen Meng (Computers and Geotechnics, 2026)

Corrigendum to “Rhizosphere priming effects and trade-offs among root traits, exudation and mycorrhizal symbioses” [Soil Biol. Biochem. 202 (2025) 109690] - He Wang; Jiayu Lu; Feike A. Dijkstra; Lijuan Sun; Liming Yin; Peng Wang; Weixin Cheng (Soil Biology and Biochemistry, 2026)

Electrochemical steering of syntrophic consortia in constructed wetlands: Dual benefits for nitrogen removal and antibiotic resistance risk control under chloramphenicol stress - Jiawei Xie; Liming Zhang; Xinyu Zhu; Lei Zhou; Weicong Wang; Shuangqi Wu; Chongjun Chen; Qiaohong Zhou; Feng Ju; Shuiping Cheng (Water Research, 2026)

Biomimetic FGFR2-decoy nanoparticles attenuate calcific aortic valve disease by targeting the FGF2/FGFR2 signaling pathway - Yulong Zhao; Liming Guo; Changzhu Li; Jiaoqi Ren; Hongyan Qiao; Cheng Wang; Xin Wen; Li Geng; Yingli Luo; Liu Yang; Guizhu Liu (Chemical Engineering Journal, 2026)

A lightweight deep learning framework for real-time smouldering forest fire detection on edge devices - Qingxuan Hou; Liming Lou; Hui Liu; Pengle Cheng; Xiaodong Liu; Ying Huang (International Journal of Remote Sensing, 2026)

Triboelectric-motorized electromagnetic conversion enables frequency upconversion and impedance reduction for low-frequency mechanical energy harvesting - Tingyu Wang; Lihua Wang; Ai Chen; Bocheng Chen; Liming Tan; Junyin Cheng; Fan Xu; Huiyuan Wu; Kaixian Li; Yilan Zhang; Yuqing Wen; Haixuan Gan; et al. (Chemical Engineering Journal, 2026)

Explainable machine learning for coagulant dosage prediction in coal port wastewater treatment - Haotian Xue; Hanrui Zhang; Mingyu Zhang; Hao Wang; Ruiling Zhang; Qian Cheng; Jingyi Zhao; Bo Wang; Liming Yuan; Shanshan Yuan; Zhenyu Song (Marine Pollution Bulletin, 2026)

Enhanced nitrogen removal and mitigated greenhouse gas emissions in bioelectrochemical system-modular moving bed wetland at low temperature: Functional zonation and multi-pathway electron transfer - Liming Zhang; Jiawei Xie; Yebin Lu; Lingwei Kong; Lei Zhou; Shuangqi Wu; Weicong Wang; Jianshi Huang; Jianfeng Li; Shuiping Cheng (Bioresource Technology, 2026)

The AT-HOOK MOTIF CONTAINING NUCLEAR LOCALIZED gene promotes somatic embryogenesis and polyploidy formation in Liriodendron hybrids - Yao Tang; Qi Zhao; Jinshu Li; Dingjie Yang; Lu Lu; Zhaodong Hao; Liming Yang; Tielong Cheng; Jisen Shi; Ying Chen; Jinhui Chen (Plant Cell Reports, 2026)

Decoding the effect of intermittent feeding strategy on the performances of modular moving bed constructed wetland: Nitrogen removal and antimicrobial resistance dissemination - Lei Zhou; Jiawei Xie; Liming Zhang; Xueqing Sui; Weicong Wang; Jianshi Huang; Shuangqi Wu; Naxin Cui; Shengbing He; Shuiping Cheng (Journal of Hazardous Materials, 2026)

Constructing a Z-scheme heterojunction on leather waste-derived biochar supporting graphitic carbon nitride for highly-efficient photocatalysis toward water decontamination - Liming Zhao; Rui Dai; Yuling Tang; Xin Cheng; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Machine learning characterization of fuel temperature and moisture dynamics in wildland-urban interface for urban fire management - Jiayue Liu; Lairong Chen; Hui Zhang; Liming Lou; Pengle Cheng; Mingyu Wang; Ying Huang (Journal of Environmental Management, 2026)

Natural deep eutectic solvent treatment for sludge deep dewatering with simultaneous enhancement of protein release at ambient temperature: Effect of tannic acid assistance - Xuan Chi; Yunbo Zhai; Cheng Huang; Xiaoping Liu; Liming Liu; Jie Hu; Changlan Hou; Piao Yang (Journal of Environmental Management, 2026)

Contrasting fine root-induced rhizosphere priming effects between coniferous and broadleaved trees - Weijun Zhang; Junjie Lin; Qitai Cheng; Liming Yin; Wenling Zhang; Amit Kumar; Xiali Mao; Hongxin Dong; Dafeng Hui; Mengguang Han; Lei Tao; Dingxin Su; et al. (Biology and Fertility of Soils, 2026)

Decoupling control of dissolved oxygen and water temperature using a state-space equation-based model predictive controller in recirculating aquaculture systems - Xinhui Zhou; Cheng Liu; Yinfeng Hao; Xianyu Zuo; Liming Zhou; Qingling Duan (Aquaculture International, 2026)

Association of plasma metals with total burden of cerebral small vessel disease: Evidence from China - Lei Zheng; Hao-Long Zeng; Ying Hui; Feipeng Cui; Yudiyang Ma; Jianing Wang; Linxi Tang; Meiqi Xing; Shuohua Chen; Liming Cheng; Shouling Wu; Zhenchang Wang; et al. (Journal of Hazardous Materials, 2026)

Remediation of mine farmland soil using hydrothermal carbonization aqueous phase from Baijiu distillers' grains: integrated benefits of metal detoxification and fertility enhancement - Piao Yang; Tao Liu; Changlan Hou; Liming Liu; Jie Hu; Cheng Huang; Wei Zou; Caixia Li; Yugui Chen; Hongmei Luo; Yunbo Zhai; Linglin Xie (Environmental Research, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Experimental study on combustion characteristics of premixed lean hydrogen flames under quantitative excitation of power ultrasound - Liming Di; Zhengtian Ren; Xuheng Yang; Jiayi Tian; Jingwei Cao; Cheng Shi (Fuel, 2026)

Potential improvement in hydrogen spherical flame propagation by ultrasonic-fed implementation under lean-burn conditions - Jian Zhu; Junjie Niu; Guohong Tian; Xuheng Yang; Liming Di; Cheng Shi (Fuel, 2026)

Differences in priming effect of topsoil versus subsoil depends on ecosystem type - Lei Tao; Liming Yin; Feike A. Dijkstra; Junjie Lin; Peng Wang; Weixin Cheng (CATENA, 2026)

Mechanism by Which Exogenous GABA Enhances the Tolerance of Potatoes to Low-Potassium Conditions - Fengjuan Wang; Ruijie Zuo; Shang Shi; Junrong Cheng; Yifei Lu; Bi Ren; Liming Lu; Liqin Li (American Journal of Potato Research, 2026)

Real-time Monitoring Unveils Three Distinct Neuronal Response Patterns to SAW Ultrasound via L-type Calcium Channels - Yiming Chen; Wenxu Tang; Yifan Wang; Ya Gao; Jiaqi Hu; Yixuan Lu; Long Meng; Hairong Zheng; Yi Feng; Liming Cheng; Wenyong Fan; Qian Cheng; et al. (Neuroscience Bulletin, 2026)

Identification of Mitochondria-Related Genes Associated with Stroke Risk Through Multi-omics Summary Data-Based MR Analysis - Xiaorong Tang; Guannan Cheng; Siyun Chen; Lulu Yao; Liming Lu; Chenwei Shen; Lubao Feng; Wenwen Zhang; Nenggui Xu; Lin Wang (Molecular Neurobiology, 2026)

Regulating phosphorus bioavailability and dissolved organic matter dynamics through deep eutectic solvent addition in distillery waste composting - Jie Hu; Yunbo Zhai; Fashen Liang; Liming Liu; Piao Yang; Cheng Huang; Changlan Hou; Xuan Chi; Hongkui He; Min Xu (Journal of Environmental Management, 2025)

Prior knowledge-informed semantic segmentation framework for precise glacial lake mapping from multimodal imagery - Huizhi Tan; Liming Jiang; Haoran Liu; Tingbin Zhang; Irene Cheng (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

A study of the effect of ammonia on the oxidation reactivity and structure of char from coal/ammonia co-pyrolysis - Dikun Hong; Yajing Guo; Changlong Qu; Yong Zhang; Liming Cui; Wenzhen Zhang; Wei Chu; Xingxing Cheng; Chunbo Wang (Fuel, 2025)

Geometrically-driven selective transport of microplastics across atmosphere-land - Shuangqi Wu; Mengrong Bao; Weicong Wang; Jianshi Huang; Chenglin Cai; Jiawei Xie; Lei Zhou; Liming Zhang; Ying Wang; Shuiping Cheng (Journal of Hazardous Materials, 2025)

Path Analysis and Multiple Linear Regression Fitting Study on Body Weight and Visceral Organ Mass of Male and Female Ussuri Catfish (Pseudobagras ussuriensis) - Qian Qi; Feng Yang; Xiaohui Sun; Chenran Lv; Shun Shi; Xiang Ding; Liming Zhao; Cheng Zhang (Fishes, 2025)
Pseudobagras ussuriensis is a valuable freshwater fish species with enormous breeding potential. To clarify the relationship between the main visceral indices and body weight in this species, 139 cultured individuals were randomly selected to measure body weight and six major organs (namely the intestine, liver, swim bladder, kidney, spleen, and gonadal), and then the causal network of internal organs and body weight of one-year-old P. ussuriensis was analyzed by path analysis, and sex-specific regression models were developed. The results showed that the correlations between body weight and the masses of the intestine, liver, swim bladder, kidney, and gonad were significant, while the spleen mass showed a significant positive correlation with body weight. Path analysis revealed that the direct path coefficients of the intestine, liver, swim bladder, kidney, and gonad on body weight were significant, and that of the spleen was significant. Through regression analysis, multiple linear regression equations were established. Importantly, the swim bladder had the greatest direct effect on body weight in males, whereas the intestine exhibited the strongest direct effect in females. These findings provide valuable insights for the selection and breeding of P. ussuriensis based on visceral indices.

Research on the oxidative decomposition of 1,2-bis(2,4,6-tribromophenoxy)ethane induced by •OH, SO4-•, and O3: Transformation mechanism, kinetics, and toxicity assessment - Yang Long; Liming Tai; Shi Yan; Jinbao Huang; Hong Wang; Xinsheng Li; Hao Cheng; Li Jin (Journal of Environmental Chemical Engineering, 2025)

High-efficiency tin perovskite solar cells through electron delocalization and defect passivation - Miao Zhang; Yong Guo; Cheng Wu; Pengyu Yan; Jialin Du; Jie Luo; Liming Ding; Feng Hao (Chemical Engineering Journal, 2025)

Associations between multiple circulating metals and clinical characteristics in lung adenocarcinoma: a hospital-based pilot study - Hao-Long Zeng; Liang Huang; Qing Yang; Jie Lu; Peng Wang; Liming Cheng (BioMetals, 2025)

Hydroxyl-driven homogeneous and robust SAM anchoring on NiOx for high-performance inverted perovskite solar cells - Xiao Wu; Haoran Yang; Ziyao Yue; Yunfan Wang; Manting Liu; Jie Zeng; Leyu Bi; Qing-Dan Yang; Yanping Huo; Liming Ding; Alex K.-Y. Jen; Sai-Wing Tsang; et al. (Chemical Engineering Journal, 2025)

Correction: Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)

Treatment of sewage sludge using choline chloride-lactic acid deep eutectic solvent: Heavy metals removal and resource recovery - Wei Zou; Liming Liu; Xiaoping Liu; Hongxia Wang; Luna Zhao; Changlan Hou; Cheng Huang; Yin Zhou; Zhexian Wang; Yunbo Zhai (Process Safety and Environmental Protection, 2025)

Assessment of the immune-developmental toxicity risk of the hygienic insecticide dimefluthrin in zebrafish (Danio rerio) model - Ruirui Li; Yang Yu; Wenxuan Cheng; Qingfeng Li; Wenping Xu; Jiagao Cheng; Liming Tao; Yang Zhang (Journal of Environmental Management, 2025)

Optimization of anode positioning in constructed wetlands coupled with microbial fuel cells based on C/O microenvironment for simultaneous removal of disinfection by-products and nitrogen - Jiawei Xie; Xue Wu; Liming Zhang; Fei Zhong; Shuiping Cheng (Journal of Hazardous Materials, 2025)

Study on Acoustic Emission-Resistivity Response of Hydraulic Fracturing in Rock-Like Samples - Jisheng Sui; Lianchong Li; Wenqiang Mu; Jian Lu; Liming Liu; Cheng Gu (Rock Mechanics and Rock Engineering, 2025)

Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)
Laminated Diatom Mats (LDMs) in the low-latitude Western Pacific provide key insights into global climate and carbon cycling. While Ethmodiscus rex ( E. rex ) LDMs research has advanced, two critical aspects remain to be elucidated: (1) the precise chronology of LDMs formation, and (2) its relationship with oceanic circulation patterns and associated nutrient flux variations. In this study, we employed AMS 14 C dating coupled with carbonate content variations to constrain the formation age of LDMs, complemented by comprehensive geochemical and clay mineral analyses of core E20, we found: (1) Diatom blooms occurred mainly from Last Glacial Maximum (LGM) to early Holocene; (2) Sediments are mostly volcanic, with increased material in E. rex layers suggesting stronger deep currents transported volcanic debris; (3) Blooms weren’t solely caused by Asian dust-derived nutrients. We propose deep current intensification and topographic upwelling drove diatom growth, highlighting deep ocean processes’ role in surface productivity and LDMs formation. This advances understanding of their climate and carbon cycle significance.

Highly oriented and efficient 2D ruddlesden-popper tin halide perovskite solar cells with enhanced intermolecular interactions - Mingyu Yin; Huanhuan Yao; Cheng Wu; Pengyu Yan; Liming Ding; Feng Hao (Chemical Engineering Journal, 2025)

Developmental and cardiotoxic effects of cyhalofop-butyl in zebrafish embryos - Bo Peng; Xinyi Zhu; Li Geng; Wenping Xu; Jiagao Cheng; Liming Tao; Yang Zhang (Food and Chemical Toxicology, 2025)

Overexpression of miR-20a targeting DUSP3 inhibits OCLN ubiquitination levels and alleviates sepsis induced intestinal barrier dysfunction - Liming Cheng; Bo Feng; Chao Xie; Chunyan Chen; Linghui Guo (In Vitro Cellular & Developmental Biology - Animal, 2025)

Fracture process of a simplified laboratory model for a cross-fault tunnel with rigid reinforcement rings: Experimental and numerical insights - Liming Tang; Chun’an Tang; Lei Cheng; Wenshuo Duan; Xu Chen; Qiang Liu (Tunnelling and Underground Space Technology, 2025)

Rhizosphere priming effects and trade-offs among root traits, exudation and mycorrhizal symbioses - He Wang; Jiayu Lu; Feike A. Dijkstra; Lijuan Sun; Liming Yin; Peng Wang; Weixin Cheng (Soil Biology and Biochemistry, 2025)

The hygienic insecticide dimefluthrin induced neurodevelopmental deficits and behavioral disorders in zebrafish (Danio rerio) larvae - Ruirui Li; Wenping Xu; Qingfeng Li; Jiagao Cheng; Zhong Li; Liming Tao; Yang Zhang (Environmental Research, 2025)

Mixed Dion-Jacobson and Ruddlesden-Popper tin halide perovskite for efficient and stable Quasi-2D Lead-Free solar cells - Mingyu Yin; Huanhuan Yao; Miao Zhang; Cheng Wu; Hongju Qiu; Liming Ding; Feng Hao (Chemical Engineering Journal, 2025)

Numerical modeling and analysis of neck injury induced by parachute opening shock - Feng Zhu; Liming Voo; Krithika Balakrishnan; Michael Lapera; Zhiqing Cheng (Medical & Biological Engineering & Computing, 2025)

Adaptive Divergence and Functional Convergence: The Evolution of Pulmonary Gene Expression in Amphibians of the Qingzang Plateau - Liming Chang; Wei Zhu; Qiheng Chen; Chunlin Zhao; Lulu Sui; Cheng Shen; Qunde Zhang; Bin Wang; Jianping Jiang (Molecular Ecology, 2025)
The Qingzang Plateau, with its harsh environmental conditions—low oxygen, high ultraviolet radiation and significant temperature fluctuations—demands specialised adaptations for survival. While genetic adaptations have been extensively studied, gene expression's role in amphibian adaptation to high elevations remains understudied. This study analysed pulmonary gene expression in 119 amphibians across the plateau to explore how genetic and environmental factors shape expression evolution. Transcriptomic analyses revealed significant interspecies variation, driven by environmental factors like temperature, oxygen levels, UVB radiation and precipitation. Principal Component and Mantel analyses found no significant correlation between gene expression divergence and genetic distance. Instead, species‐specific traits and environmental pressures were pivotal in shaping expression patterns. PERMANOVA analysis showed environmental factors had varying impacts on species. For instance, Bufo gargarizans exhibited a strong gene expression response to multiple environmental factors, while Scutiger boulengeri was less influenced, reflecting diverse adaptive strategies. Functional enrichment analysis highlighted convergence in key biological processes, such as energy metabolism, apoptosis and autophagy, despite species‐specific gene expression differences. These processes are critical for surviving the plateau's extremes. The findings suggest that gene expression evolution in amphibians on the Qingzang Plateau is shaped by both genetic diversity and environmental pressures. Although gene expression profiles vary, they converge on essential functions, offering insights into adaptation mechanisms in extreme environments.

Genetic estimation of fat traits in sheep and association of its NR1H4 gene polymorphisms with tail fat deposition - Kunchao Han; Fadi Li; Xiaoxue Zhang; Huibin Tian; Deyin Zhang; Kai Huang; Yuan zhao; Yukun Zhang; Liming Zhao; Dan Xu; Jiangbo Cheng; Zongwu Ma; et al. (Small Ruminant Research, 2025)

PbI2 intercalation and residual elimination strategy for sequential inverted perovskite solar cells - Zhuowei Du; Zhu Ma; Tangjie Yu; Zhangfeng Huang; Shanyue Hou; Qianyu Liu; Yanlin Li; Yi Chen; Qiang Yang; Wei You; Junbo Yang; Hao Du; et al. (Chemical Engineering Journal, 2025)

A Meta‐Analysis of Bycatch Mitigation Methods for Sea Turtles Vulnerable to Swordfish and Tuna Longline Fisheries - Hao Yan; Cheng Zhou; Eric Gilman; Jie Cao; Rong Wan; Fan Zhang; Jiangfeng Zhu; Liuxiong Xu; Liming Song; Xiaojie Dai; Siquan Tian (Fish and Fisheries, 2025)
Fisheries bycatch poses one of the most significant threats to sea turtles. Although various methodologies have been developed to mitigate sea turtle bycatch in swordfish and tuna longline fisheries, the effectiveness and interactions remain uncertain. In this study, we conducted a comprehensive meta‐analysis, encompassing 41 studies focused on sea turtles and 36 studies on tunas, swordfish and sharks, all derived from well‐controlled experimental research in swordfish and tuna longline fisheries. The objective was to systematically evaluate the relative effectiveness of species‐specific mitigation strategies for sea turtles, particularly examining the impact of circle hooks and fish bait as alternatives to conventional longline fishing practices. While a nuanced hierarchy, characterised by species‐specific patterns, was observed among the mitigation measures, circle hooks demonstrated great promise in reducing bycatch of loggerhead, olive ridley and leatherback turtles, with minimal impact on the catch rates of tuna, swordfish and sharks. We highlighted the broader applicability of fish bait in minimising sea turtle bycatch, noting that the effectiveness of bait may overlap with that of hooks, potentially making the additional benefits of the hooks less evident. The study also revealed regional variations in the effectiveness of these methods, emphasising the need for more detailed data collection. Given current data limitations that restrict extensive meta‐analyses, a series of small‐sample studies with promising innovations, exemplified by circle hooks with a wire appendage and blue‐white lights, necessitates in‐depth investigation and field tests.

Rhizosphere priming and effects on mobilization and immobilization of multiple soil nutrients - Jiayu Lu; Jiangping Cai; Feike A. Dijkstra; Liming Yin; Peng Wang; Weixin Cheng (Soil Biology and Biochemistry, 2024)

The influence of vermicompost on atrazine microbial degradation performance and pathway in black soil, Northeast China - Xia Hou; Yang Ou; Xinhong Wang; Huiping Liu; Lei Cheng; Liming Yan (Science of The Total Environment, 2024)

Multi-objective optimization of distributed green infrastructure for effective stormwater management in space-constrained highly urbanized areas - Hong Zhou; Cheng Gao; Qinghua Luan; Liming Shi; Zhengsheng Lu; Jun Liu (Journal of Hydrology, 2024)

Efficient phosphorus recovery from waste activated sludge: Pretreatment with natural deep eutectic solvent and recovery as vivianite - Luna Zhao; Liming Liu; Xiaoping Liu; Aoqiang Shu; Wei Zou; Zhexian Wang; Yin Zhou; Cheng Huang; Yunbo Zhai; Hongkui He (Water Research, 2024)

Natural pyrethrins induced developmental toxicity of zebrafish swim bladder in vivo and genotoxicity of lung cells in vitro - Ruirui Li; Cheng Zhang; Wenping Xu; Liming Tao; Jiagao Cheng; Zhong Li; Yang Zhang (Toxicology in Vitro, 2024)

Cardiotoxicity risk induced by sanitary insecticide Dimefluthrin - Ruirui Li; Ning Zhou; Cheng Zhang; Mengqi Wu; Wenping Xu; Jiagao Cheng; Liming Tao; Zhong Li; Yang Zhang (Chemosphere, 2024)

Expression of ovine MYH3 gene and its polymorphisms and association analysis with growth traits in Hu sheep - Kunchao Han; Fadi Li; Xiaoxue Zhang; Huibin Tian; Deyin Zhang; Kai Huang; Yukun Zhang; Yuan Zhao; Liming Zhao; Dan Xu; Jiangbo Cheng; Zongwu Ma; et al. (Small Ruminant Research, 2024)

Effect of liquid ammonia HPDI strategies on combustion characteristics and emission formation of ammonia-diesel dual-fuel heavy-duty engines - Zheng Zhang; Liming Di; Lei Shi; Xiyu Yang; Tengfei Cheng; Cheng Shi (Fuel, 2024)

Coupled of carbon and nitrogen mineralization in rhizosphere soils along a temperate forest altitudinal gradient - Changfu Huo; Jiayu Lu; Liming Yin; Peng Wang; Weixin Cheng (Plant and Soil, 2024)

Effect of inlet velocity on the hydraulic and filtering performance of a Y‐type screen filter - Na Li; Junfeng Li; Liming Yu; Wenhan Yang; Xuelian Liu; Qiao Cheng (Irrigation and Drainage, 2024)
Uneven sediment distribution affected by inlet velocity, particle size distribution and flow field characteristics leads to local clogging in a Y‐type screen filter. This study revealed the detailed flow field characteristics and distribution of sediments on the screen via computational fluid dynamics combined with the discrete element method (CFD–DEM) simulations and experimental tests. The results showed that the distribution of the flow rate on the filter screen was extremely uneven, with the maximum flow rate being 11.72 times greater than the minimum rate. The flow rate was distributed symmetrically on the two sides along the outlet centreline, as shown by the unfolded drawing of the filter core. Numerical simulation and experimental tests using sandy water showed that the number and average particle diameter on the screen decreased, and the number and average particle diameter in the plug increased, with increasing inlet velocity. The sediments on the screen were distributed intensively, and the plugging extent coefficient and the anti‐clogging performance improved. However, this process was more likely to cause local clogging and worsen the filtration performance. Therefore, low‐speed filtering should be applied if the filtering effect is needed, and high‐speed filtering should be applied if the filtering efficiency is favourable but the flushing frequency increases.

Efficient removal of heavy metals from sewage sludge using a low-cost protic ionic liquid: Investigation of mechanism and ecological risk - Hongxia Wang; Yunbo Zhai; Liming Liu; Xiaoping Liu; Zhexian Wang; Yin Zhou; Cheng Huang; Hongkui He (Journal of Environmental Chemical Engineering, 2024)

Super-adiabatic temperature gradient at Jupiter's equatorial zone and implications for the water abundance - Cheng Li; Michael Allison; Sushil Atreya; Shawn Brueshaber; Leigh N. Fletcher; Tristan Guillot; Liming Li; Jonathan Lunine; Yamila Miguel; Glenn Orton; Paul Steffes; J. Hunter Waite; et al. (Icarus, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

Deep eutectic solvents pretreatment enhances methane production from anaerobic digestion of waste activated sludge: Effectiveness evaluation and mechanism elucidation - Yu Xie; Xiaoping Liu; Liming Liu; Yin Zhou; Zhexian Wang; Cheng Huang; Hongkui He; Yunbo Zhai (Journal of Environmental Management, 2024)

Cr and N co-doped biochar driving controllable peroxydisulfate activation pathways to degrade tetracycline: Pyrrolic N inducing singlet oxygen generation - Lijun Guo; Liming Zhao; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2024)

Enhancing bioavailable carbon sources and minimizing ammonia emissions in distillery sludge and distiller's grains waste co-composting through deep eutectic solvent addition - Fashen Liang; Xiaoping Liu; Xin Yu; Liming Liu; Hongkui He; Cheng Huang; Jie Hu; Zhexian Wang; Yin Zhou; Yunbo Zhai (Bioresource Technology, 2024)

Removal of low concentration of perchlorate from natural water by quaternized chitosan sphere (CGQS): Efficiency and mechanism research - Shiyun Jin; Liming Liu; Shanhong Li; Yin Zhou; Cheng Huang; Zhexian Wang; Yunbo Zhai (Journal of Hazardous Materials, 2024)

Hepatic effects of acetochlor chiral isomers in zebrafish and L02 cells - Xin Wang; Bo Peng; Cheng Zhang; Mengqi Wu; Wenping Xu; Jiagao Cheng; Liming Tao; Zhong Li; Yang Zhang (Science of The Total Environment, 2024)

Impact of effective impervious surface disconnection on urban hydrographs: A multi-scenario modeling study at the catchment scale - Hong Zhou; Jun Liu; Shufang Ou; Cheng Gao; Yi Zhou; Liming Shi; Kai Zhou (Journal of Hydrology, 2024)

Stereoselective toxicity of acetochlor chiral isomers on the nervous system of zebrafish larvae - Xin Wang; Shoulin Li; Cheng Zhang; Wenping Xu; Mengqi Wu; Jiagao Cheng; Zhong Li; Liming Tao; Yang Zhang (Journal of Hazardous Materials, 2024)

Developmental toxicity and estrogenicity of glyphosate in zebrafish in vivo and in silico studies - Jian Lu; Cheng Zhang; Wenping Xu; Weidong Chen; Liming Tao; Zhong Li; Jiagao Cheng; Yang Zhang (Chemosphere, 2023)

Elevated CO2 and nitrogen interactively affect the rhizosphere priming effect of Cunninghamia lanceolata - Qiufeng Xu; Jiayu Lu; Feike A. Dijkstra; Liming Yin; Peng Wang; Weixin Cheng (Soil Biology and Biochemistry, 2023)

Glial Activation, Mitochondrial Imbalance, and Akt/mTOR Signaling May Be Potential Mechanisms of Cognitive Impairment in Heart Failure Mice - Yanan Wu; Kaiyi Zhou; Baiyang Liu; Jindong Xu; Liming Lei; Jiaqi Hu; Xiao Cheng; Feng Zhong; Sheng Wang (Neurotoxicity Research, 2023)

Characterization of hepatotoxic effects induced by pyraclostrobin in human HepG2 cells and zebrafish larvae - Mengqi Wu; Jinhao Bian; Shuang Han; Cheng Zhang; Wenping Xu; Liming Tao; Zhong Li; Yang Zhang (Chemosphere, 2023)

Molecular mechanisms of cardiotoxicity induced by acetamide and its chiral isomers - Xin Wang; Li Geng; Mengqi Wu; Wenping Xu; Jiagao Cheng; Zhong Li; Liming Tao; Yang Zhang (Science of The Total Environment, 2023)

The various effect of cow manure compost on the degradation of imazethapyr in different soil types - Lei Cheng; Lixia Wang; Xinhong Wang; Yang Ou; Huiping Liu; Xia Hou; Liming Yan; Xinyi Li (Chemosphere, 2023)

Linking plant traits to rhizosphere priming effects across six grassland species with and without nitrogen fertilization - Jiayu Lu; Liming Yin; Feike A. Dijkstra; Shaobin Yan; Peng Wang; Weixin Cheng (Soil Biology and Biochemistry, 2023)

Assessment of 13 essential and toxic trace elements in tumor and peritumoral brain tissues from human glioblastoma - Hao-Long Zeng; Binmei Jia; Qing Yang; Fengbo Zeng; Huijun Li; Chao-Xi Li; Liming Cheng (JBIC Journal of Biological Inorganic Chemistry, 2023)

Dietary fish and omega-3 polyunsaturated fatty acids intake and cancer survival: A systematic review and meta-analysis - Yi Wang; Ke Liu; Tingting Long; Jieyi Long; Ying Li; Jiaoyuan Li; Liming Cheng (Critical Reviews in Food Science and Nutrition, 2023)

Virus impacted community adaptation in oligotrophic groundwater environment revealed by Hi-C coupled metagenomic and viromic study - Zhanwen Cheng; Xiang Li; Alejandro Palomo; Qing Yang; Long Han; Ziqi Wu; Zengyi Li; Miao Zhang; Liming Chen; Bixi Zhao; Kaiqiang Yu; Chuanlun Zhang; et al. (Journal of Hazardous Materials, 2023)

Multi-scale multivariate detection method for the effective impact range of hydraulic fracturing in coal seam - Yujie Peng; Liming Qiu; Yi Zhu; Qiang Liu; Dazhao Song; Xiaohe Cheng; Chaojie Wang; Yingjie Liu; Qian Sun (Journal of Applied Geophysics, 2023)

Interaction of metabolism-related pathway gene variants with bisphenol A exposure on serum lipid profiles - Heng He; Fuwei Zhang; Shuang Zhou; Shanshan Zhang; Lu Wang; Jiaoyuan Li; Qiang Zeng; Ying Zhu; Jianbo Tian; Jiang Chang; Liming Cheng; Qing Lu; et al. (Environmental Toxicology and Pharmacology, 2023)

Characterization of acetochlor degradation and role of microbial communities in biofilters with varied substrate types - Huiping Liu; Xinhong Wang; Yang Ou; Lei Cheng; Xia Hou; Liming Yan; Liping Tian (Chemical Engineering Journal, 2023)

Highly effective recovery of palladium from a spent catalyst by an acid- and oxidation-resistant electrospun fibers as a sorbent - Nianshou Cheng; Lin Zhang; Mingyue Wang; Jiancheng Shu; Penghui Shao; Liming Yang; Xiaojing Meng; Yuzhu Fan; Min Li (Chemical Engineering Journal, 2023)

Expression profiles of the CD274 and PLEKHH2 gene and association of its polymorphism with hematologic parameters in sheep - Yukun Zhang; Xiaoxue Zhang; Fadi Li; Changchun Lin; Deyin Zhang; Benzhen Duan; Yuan Zhao; Xiaolong Li; Dan Xu; Jiangbo Cheng; Liming Zhao; Jianghui Wang; et al. (Veterinary Immunology and Immunopathology, 2023)

An insight into direct water injection applied on the hydrogen-enriched rotary engine - Cheng Shi; Sen Chai; Huaiyu Wang; Changwei Ji; Yunshan Ge; Liming Di (Fuel, 2023)

Priming effect on soil carbon decomposition by root exudate surrogates: A meta-analysis - Shaobin Yan; Liming Yin; Feike A. Dijkstra; Peng Wang; Weixin Cheng (Soil Biology and Biochemistry, 2023)

Identification of the relatively low permeability area in coal and gas outburst seams by seismic wave tomography technique: Field application and validation - Yingjie Zhao; Xueqiu He; Dazhao Song; Liming Qiu; Xiaohe Cheng; Zhenlei Li; Shengquan He (Journal of Applied Geophysics, 2023)

A multi-criteria analysis framework for water transfers to improve the water environments under strong artificial interventions in highly urbanized areas - Hong Zhou; Jun Liu; Shufang Ou; Yongjie Shi; Cheng Gao; Liming Shi; Can Jin (Environmental Research, 2023)

Soy protein isolate-catechin non-covalent and covalent complexes: Focus on structure, aggregation, stability and in vitro digestion characteristics - Shicheng Dai; Peilong Liao; Yilun Wang; Tian Tian; Xiaohong Tong; Bo Lyu; Lin Cheng; Liming Miao; Weijie Qi; Lianzhou Jiang; Huan Wang (Food Hydrocolloids, 2023)

Analytical method for the kinematic response and signal error of a downhole seismometer subjected to P-waves - Changwei Yang; Cheng Yuan; Liming Qu; Xuanming Ding (Soil Dynamics and Earthquake Engineering, 2023)

Association of whole blood metals/metalloids with severity in sepsis patients: A prospective, single-center, pilot study - Bo Zhang; Qing Yang; Xu Wang; Bingmei Jia; Liming Cheng; Hao-Long Zeng (Journal of Trace Elements in Medicine and Biology, 2023)

Halogen engineering of 2D/3D tin halide perovskite for enhanced structural stability - Huanhuan Yao; Weike Zhu; Jie Hu; Cheng Wu; Shurong Wang; Xuhong Zhao; Xiaobin Niu; Liming Ding; Feng Hao (Chemical Engineering Journal, 2023)

Microseismic Monitoring of Hydraulic Fracture Propagation and Seismic Risks in Shale Reservoir with a Steep Dip Angle - Zhaohui Lu; Yunzhong Jia; Lijun Cheng; Zhejun Pan; Liangjun Xu; Pei He; Xiaozhong Guo; Liming Ouyang (Natural Resources Research, 2022)

Identification of RNA helicases in Medicago truncatula and their expression patterns under abiotic stress - Jie Cheng; Songsong Zhou; Kun Yang; Hongyang Yu; Rongrong Chen; Liming Zeng; Hua Li; Yihua Wang; Jianbo Song (Physiology and Molecular Biology of Plants, 2021)

Genetic removal of the CH1 exon leads to the production of hypofunctional heavy chain-only IgG2a in rats - Zhenrong Li; Ming Zhang; Shunan Zheng; Yu Song; Xueqian Cheng; Di Yu; Lijuan Du; Liming Ren; Haitang Han; Yaofeng Zhao (Transgenic Research, 2020)

Analysis of urinary trace element levels in general population of Wuhan in central China - Hao-Long Zeng; Chang-Wen-Bo Liu; Jie Lu; Xu Wang; Liming Cheng (Environmental Science and Pollution Research, 2019)

Assessment of 12 Metals and Metalloids in Blood of General Populations Living in Wuhan of China by ICP-MS - Hao-Long Zeng; Huijun Li; Jie Lu; Qing Guan; Liming Cheng (Biological Trace Element Research, 2019)

Prediction of Biodegradability for Polycyclic Aromatic Hydrocarbons Using Various In Silico Modeling Methods - Gong Cheng; Liming Sun; Jie Fu (Archives of Environmental Contamination and Toxicology, 2018)

Ecological effects of rice-duck integrated farming on soil fertility and weed and pest control - Qing Teng; Xue-Feng Hu; Chang Cheng; Zhiqing Luo; Fan Luo; Yong Xue; Yijun Jiang; Zhen Mu; Liming Liu; Minyong Yang (Journal of Soils and Sediments, 2016)

Influences of introducing frogs in the paddy fields on soil properties and rice growth - Qing Teng; Xue-Feng Hu; Fan Luo; Chang Cheng; Xinyi Ge; Minyong Yang; Liming Liu (Journal of Soils and Sediments, 2016)

The Effects of Oxidative Stress on the Compressive Damage Thresholds of C2C12 Mouse Myoblasts: Implications for Deep Tissue Injury - Yifei Yao; Zhitao Xiao; Singwan Wong; Yu-Chun Hsu; Truman Cheng; Chih-Chieh Chang; Liming Bian; Arthur F. T. Mak (Annals of Biomedical Engineering, 2015)

Gadolinium promoted proliferation in mouse embryo fibroblast NIH3T3 cells through Rac and PI3K/Akt signaling pathways - Liming Shen; Aochu Yang; Pengwei Yao; Xiaohong Sun; Cheng Chen; Cuiping Mo; Lei Shi; Youjiao Chen; Qiong Liu (BioMetals, 2014)

Identifying gene expression profile of spinal cord injury in rat by bioinformatics strategy - Lingjing Jin; Zhourui Wu; Wei Xu; Xiao Hu; Jin Zhang; Zhigang Xue; Liming Cheng (Molecular Biology Reports, 2014)

Secretory/releasing proteome-based identification of plasma biomarkers in HBV-associated hepatocellular carcinoma - Lei Yang; WeiQi Rong; Ting Xiao; Ying Zhang; Bin Xu; Yu Liu; LiMing Wang; Fan Wu; Jun Qi; XiuYing Zhao; HongXia Wang; NaiJun Han; et al. (Science China Life Sciences, 2013)

Monitoring and assessing reclamation settlement in coastal areas with advanced InSAR techniques: Macao city (China) case study - Liming Jiang; Hui Lin; Shilai Cheng (International Journal of Remote Sensing, 2011)

QTLs of cold tolerance-related traits at the booting stage for NIL-RILs in rice revealed by SSR - Yawen Zeng; Shuming Yang; Hong Cui; Xiaojuan Yang; Liming Xu; Juan Du; Xiaoying Pu; Zichao Li; Zaiquan Cheng; Xingqi Huang (Genes & Genomics, 2009)

Spatial dependence of diurnal temperature range trends on precipitation from 1950 to 2004 - Liming Zhou; Aiguo Dai; Yongjiu Dai; Russell S. Vose; Cheng-Zhi Zou; Yuhong Tian; Haishan Chen (Climate Dynamics, 2009)

Spatial dependence of diurnal temperature range trends on precipitation from 1950 to 2004 - Liming Zhou; Aiguo Dai; Yongjiu Dai; Russell S. Vose; Cheng-Zhi Zou; Yuhong Tian; Haishan Chen (Climate Dynamics, 2009)

The Dependence of Benzo-15-Crown-5 Ether-Containing Oligo Paraphenylene Vinylene (CE-OPV) Emission Upon Complexation with Metal Ions in Solution - Gowri Ramachandran; George Simon; Yibing Cheng; Trevor A. Smith; Liming Dai (Journal of Fluorescence, 2003)